Simulated modeling and image processing for intra-cardiac interventional diagnosis and therapy - Chiang, Patricia Wei Yin (2013)
Coronary angioplasty and intra-coronary stent implantation are minimally invasive procedures to treat coronary heart disease through revascularization. A percutaneous intra- cardiac intervention offers an alternative treatment to restore myocardial function in ischemic regions through stem cell injection. This procedure allows for diagnosis and therapy in the same surgical setting where electromechanical mapping of the heart can detect ischemic regions and assess their severity for treatment.